Block-copolymer assisted fabrication of anisotropic plasmonic nanostructures. (25th June 2018) - Gunder, Calbi; Dhara, Pijiush K; Manna, Uttam; Biswas, Mahua
Abstract: The anisotropic nanostructures of noble metals are of great interest for plasmonic applications, due to the possibility of tuning the localized surface plasmon resonance (LSPR) across the UV–visible–near infrared (UV–vis-NIR) without sacrificing the linewidth, as well as achieving larger local field enhancement. Here, we report a simple and promising fabrication method of anisotropic gold nanostructures film using polystyrene-b-poly(2vinylpyridine) (PS-b-P2VP) block copolymers (BCPs) as a template. In this approach, PS-b-P2VP spherical micelles were first synthesized as a template, followed by selective deposition of an Au precursor inside the P2VP core of the micelles, using an ethanol solution of Au salt. Subsequently, heat treatment of the precursor deposited BCP films followed by the removal of the BCP template produced anisotropic gold nanostructures of various shapes, such as octahedron, decahedron, tetrahedron, triangles, and triangular prism. A temperature and time dependent study during heat treatment shows the formation of clusters at a higher temperature. Furthermore, measurements of the ensemble extinction spectra of the anisotropic Au nanoparticle films showed two broad distinct LSPR peaks; one in the visible range (∼660 nm), and the other in the NIR range (∼875 nm). The electrodynamic simulation showed that octahedron and decahedron nanoparticles are responsible for the LSPR response in the visible; whereas the triangular shapes are responsible for the LSPR response in the NIR. Our work is expected to open up a new direction for the synthesis of anisotropic nanostructures of noble metals, that can be utilized to tune the LSPR response across the UV–vis-NIR range, using a simple BCP template-based method.